Gluing osteochondral fragments: development of a novel strategy for dual adhesive application in a preclinical model - Bojan, Alicja J.; Karami, Peyman; Procter, Philip; Pioletti, Dominique P. (Frontiers in Medical Engineering, 2024)
This study proposes a novel dual adhesive approach for fixing osteochondral fractures, aiming to address the limitations of current fixation methods by incorporating both a bone adhesive (phosphoserine modified calcium phosphate cement PM-CPC) and a cartilage adhesive (methacrylated phosphoserine-containing gelatin MePGa hydrogel). The feasibility and efficacy of this approach were investigated using an ex vivo bovine knee model. Results indicate successful gluing of osteochondral cylinders with both adhesives, with no significant difference in adhesion strength between the groups (adhesion strength mean of 1211.6 kPa, SD 602.4 kPa, and mean of 1299.6 kPa, SD 850.9 kPa for groups 1 and 2 respectively). Importantly, the inclusion of the hydrogel component in the dual adhesive system aims to enhance cartilage repair potential, complementing the mechanical support provided by the bone adhesive. Each adhesive offers distinctive benefits: PM-CPC for mechanical support and bone repair, and MePGa hydrogel for cartilage repair. The study demonstrates the potential of the dual adhesive strategy for osteochondral repair, though further refinement and in vivo validation are needed.